Desempenho de bovinos da raça Gir em pastagem de Brachiaria brizantha submetidos a diferentes manejos - Fernandes, Leonardo De Oliveira; Reis, Ricardo De Andrade; Paes, José Mauro Valente; Teixeira, Rafael Monteiro Araújo; Queiroz, Domingos Sávio; Paschoal, Juliana Jorge (UFBA - Universidade Federal da Bahia, 2015)
This research aimed to evaluate the effect of protein and energy supplementation and different herbage allowances (OF) during the rainy season, on the weight gain of Gir young bulls grazing Brachiaria brizantha maintained in a rotational grazing system. Evaluated forage allowance and chemical composition of Brachiaria brizanthapasture. We used 24 Gir young bulls with an average weight of 223kg, distributed in a randomized block design in a split plot scheme, treatments was distributed in plots, and periods in subplots, with six replications. Treatments were not supplemented (SS) young bull grazing in pasture with 4.0% of forage allowance (SS + 4% FA); supplementation with 0.5% body weight (SO) and 4.0% of FA (SO + 4.0 % FA); supplementation with 0.5% body weight and 3.5% FA (SO + 3.5% FA) and supplementation with 0.5% body weight and 4.5% FA (SO + 4.5% FA). During the rainy season, the young bulls weight gain increased (P <0.05) in response to supplementation (0.848, 0.813 and 0.905kg/ day), respectively in the animals of the S0 + 4% OF; SO + 3.5 and SO OF% OF + 4.5, compared to those not supplemented (0.567kg/day). Animals of the SO+ 4.5% OF showed higher gain compared to the SO + 4.0% OF and SO + 3.5% OF. Pasture management strategies and supplementation did not affect the forage chemical composition (P>0.05).

O objetivo com este trabalho foi avaliar o efeito da suplementação protéico-energética e diferentes ofertas de forragem (OF) durante o período das águas, sobre o ganho de peso de bovinos da raça Gir manejados em sistema de lotação rotacionada em Brachiaria brizantha cv. Marandu. Avaliou-se a disponibilidade e a composição química do capim Brachiaria brizantha cv. Marandu. Foram utilizados 24 bovinos da raça Gir com peso médio de 223kg, distribuídos em um delineamento em blocos ao acaso, em parcela subdividida, alocando os tratamentos nas parcelas e os períodos nas subparcelas, com quatro tratamentos e seis repetições. Os tratamentos foram: novilhos sem suplementação (SS) mantidos em pastos com 4,0% do peso corporal (PC) de OF (SS + 4,0% OF); tourinhos suplementados (SO) com concentrado em 0,5% do peso corporal (PC) e 4% do PC de OF (SO + 4,0%OF); tourinhos suplementados com concentrado em 0,5% do PC e 3,5% do PC de OF (SO + 3,5% OF) e tourinhos suplementados com concentrado em 0,5% do PC e 4,5% do PC de OF (SO + 4,5%OF). Foi verificado, durante o período das águas, aumento (P < 0,05) no ganho de peso dos novilhos suplementados (0,848, 0,813 e 0,905kg/dia, respectivamente nos tratamentos SO + 4%OF; SO + 3,5%OF e SO + 4,5%OF) comparado aos novilhos que não receberam suplementação (0,567kg/dia). Os animais do tratamento SO + 4,5%OF apresentaram maior ganho comparados aos do SO + 4%OF e SO + 3,5%OF. Não houve efeito dos tratamentos sobre a composição química da forragem (P>0,05).
Performance of Gir young bull maintained in Brachiaria brizantha pastures submitted to different management
Keywords: rotational grazing; supplementation; tropical grass; weight gain; ganho de peso; gramínea tropical; pastejo rotacionado; suplemento